A75: Proposal of the Bristol Criteria for the Diagnosis of Chronic Non‐bacterial Osteitis From a Cohort of 41 Patients. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Ramanan, Athimalaipet V; Roderick, Marion; Shah, Ripal; Finn, Adam
Abstract : Background/Purpose: Chronic recurrent multifocal osteomyelitis (CRMO) is an inflammatory bone disease occurring primarily in children and adolescents. Delays in referral and diagnosis may lead to prolonged courses of antibiotics with in‐patient care, substantial radiation exposure from multiple plain radiographs or bone scans and bone biopsies which may be repeated. Methods: Children (aged less than 18 years) diagnosed with CRMO between January 2005 and December 2012, who were reviewed at Bristol Royal Hospital for Children were included; their clinical notes reviewed, laboratory, histopathology and radiology data were extracted. We retrospectively applied the Bristol criteria for diagnosis (table1 ). Results: Forty one patients (Female: Male ratio 31:10) were diagnosed as CRMO and assessed at the Bristol centre over the 8 year period. The onset of symptoms occurred at a median of 9 years with a delay in diagnosis with a median of 15 months (range 0–92). Initial plain radiograph was abnormal in 28 out of 36 patients; whole body MRI (WB‐MRI) detected lesions in seven of the patients with normal plain radiograph. 162 lesions were identified by imaging, of which, 47 were asymptomatic and detected only by MRI. After imaging, only ten patients (24%) had a solitary lesion (six of which were clavicle alone). From the data, diagnostic criteria were developed. Using the proposed criteria retrospectively, thirty‐four children could have potentially been diagnosed by criterion 1, with 6 children requiring a biopsy (criterion 2) for diagnosis, either for a solitary lesion not clavicle or atypical features such as age. Bone biopsies in our cohort had been repeated in a third of patients prior to referral. Thirteen children completed at least one year of pamidronate treatment with MRI available both before and after treatment on eleven of these. After a year of pamidronate therapy, 71% of lesions improved and 29 % remained stable on MRI scans. Around 20%–30% patients having pamidronate therapy will continue to have troublesome symptoms. Conclusion: We suggest that using the Bristol diagnostic criteria (table1 ) with an experienced clinician may obviate the need for biopsy in some patients. Pamidronate was found to be a useful second‐line agent with objective MRI evidence of benefit.